EDUCATION 5.0 AND THE CHALLENGES OF THE ALPHA GENERATION IN THE FACE OF LIQUID MODERNITY (Editora Impacto Científico, 2025)
Education 5.0 involves considerable challenges within Liquid Modernity, in which the only certainty is instability. Furthermore, adding to the reality of efficiently educating the “Alpha Generation”, which is the main recipient of educational work, the challenges are heightened. In this way, the present study aims to highlight reflections on this 21st Century education, due to the characteristics of current modernity and the new generation of students, known as “digital natives”, who have a different attitude from previous generations. Pointing out who these students are, what their characteristics are and the impact generated in the teaching-learning process becomes fundamental for reflecting on the meaning of Education 5.0. The “Alpha Generation” needs to be studied and understood by institutions and teachers, so that they, combined with technological resources, offer the best service that results in the good delivery of results by students within the academic context and later in the job market, generating a collaborative and learning environment. To develop the work, a qualitative bibliographical research was carried out on some academic materials, where in the end, it was concluded that modernity has characteristics of the “BANI” and “VUCA” Worlds, which will be covered, but mainly is governed by the Liquid World, led by the generation of Alpha students, who require special attention from teachers and educational institutions.